Synthesis, in vitro and in vivo biological evaluation of novel graveolinine derivatives as potential anti-Alzheimer agents. Issue 1 (1st January 2020) - Luo, Wen; Lv, Jian-Wu; Wang, Ting; Zhang, Zhi-Yang; Guo, Hui-Yan; Song, Zhi-Yi; Wang, Chao-Jie; Ma, Jing; Chen, Yi-ping
Graphical abstract: Highlights: A novel series of graveolinine derivatives were synthesized and evaluated as potential anti-Alzheimer's agents. Compound 5f showed moderate inhibitory activities for AChE, BuChE and Aβ self-aggregation. Compound 5f significantly ameliorates the cognitive performances of scopolamine-treated ICR mice. Abstract: A novel series of graveolinine derivatives were synthesized and evaluated as potential anti-Alzheimer agents. Compound 5f exhibited the best inhibitory activity for acetylcholinesterase (AChE) and had surprisingly potent inhibitory activity for butyrylcholinesterase (BuChE), with IC50 values of 0.72 μM and 0.16 μM, respectively. The results from Lineweaver–Burk plot and molecular modeling study indicated non-competitive inhibition of AChE by compound 5f . In addition, these derivatives showed potent self-induced β-amyloid (Aβ) aggregation inhibition. Moreover, 5f didn't show obvious toxicity against PC12 and HepG2 cells at 50 μM. Finally, in vivo studies confirmed that 5f significantly ameliorates the cognitive performances of scopolamine-treated ICR mice. Therefore, these graveolinine derivatives should be thoroughly and systematically studied for the treatment of Alzheimer's disease.